GONG BETINO DAN GONG JANTAN: KONSTRUKSI GENDER PADA ALAT MUSIK GONG BULUH KERINCI - Amor Seta Gilang Pratama; Masvil Tomi; Dwi Rahariyoso (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2022)
This research focuses on the relationship between the cultural structure of Kerinci, and the Gong Buluh traditional music. What is being explored is how material culture is, also seen in treating the reed gong as a traditional musical instrument in Kerinci. The method used in this research is a qualitative method with a case study approach. The process of collecting data is by conducting ethnographic interviews. Ethnographic interview is a type of interview that is not too formal, friendly, but inserts ethnographic questions, such as questions that are descriptive, structural, and contrast. There are two stages of data analysis technique. The first stage is to codify the data that has been obtained. The second stage is to carry out an analysis between data, to see the relationship between the structure of the kerinci culture and Gong Buluh, using the theory or concept that has been referred to. The results of the study show that epistemologically, the structure of the reed gong is divided into two parts, namely the gong betina and the gong jantan. Gong betina have a higher sound intensity than gong jantan. The terms betina and jantan in the context of the gong become a duality related to the structure of the Kerinci culture. The Kerinci tribe adheres to a materiallineal system, in which women (ninik mamak, inner child) are the highest customary authority holders. The structure of the gong reed thus has a similarity to the construction of the Kerinci culture which is the basis and convention in rituals traditions, especially Kenduri Sko.